Effects of Cr3+ on the corrosion of SiC in LiF–NaF–KF molten salt. (January 2017) - Xue, Wandong; Yang, Xinmei; Qiu, Jie; Liu, Huajian; Zhao, Bin; Xia, Huihao; Zhou, Xingtai; Huai, Ping; Liu, Hongtao; Wang, Jianqiang
Highlights: Effect of Cr 3+ on the corrosion of SiC in LiF-NaF-KF molten salt was investigated. Cr 3+ in LiF-NaF-KF molten salt can aggravate the corrosion of SiC. The thickness of corroded region in salt with Cr 3+ is much larger than that in pure salt. The corroded region is composed of Cr2 C3, Cr7 C3, Cr2 O3, and graphitic carbon. Corrosion induced by Cr 3+ should be attributed to reactions of Cr 3+ with SiC. Abstract: Effects of Cr 3+ on the corrosion of SiC in LiF–NaF–KF molten salt were investigated. Results reveal that Cr 3+ can drive the corrosion of SiC. Thickness of the corroded region induced by Cr 3+ is greater than 12 μm for 400 h, while the corroded region induced by pure salt is ∼2.5 μm. Corrosion induced by Cr 3+ should be attributed to the reactions of Cr 3+ with SiC. Cr 3+ reacts with SiC to form Cr3 C2, Cr7 C3, and graphitic carbon in the corroded region of SiC, which results in the dissolution of element Si from SiC into the salt.